Los grandes artistas : pintores italianos ((Biblioteca Popular de Arte))
Contenido: Giotto, Juan Bellini, El Perugino, Leonardo de Vinci, Rafael, Miguel Angel, Andrés del Sarto, Giorgione, Correggio, Tiziano, Pablo Veronés, El Dominiquino, Albano y Salvator Rosa.